The Evolution of Resin-Based Dental Materials/Composites: The Way Forward - Danish, Syed Mohammad; Habib, Imran (Journal of Orofacial Research, 2018)
Composites have come a long way since replacement of silicates as the material of choice in restorative and esthetic dentistry. The qualities of the resin-based material have immensely increased in the context of bonding and curing mechanisms. Due to its esthetic qualities, the composite has left behind many restorative materials and become the number one choice in the field of esthetic dentistry. Still, a lot needs to be done to reduce the limitations of composites like expansion or shrinkage, optimization of composites according to amorphous calcium phosphate, incorporation of antibacterial properties in composites and enhancement of self-adhesive properties. Fortuitously, an ample amount of research is done in this area in recent years and as a result, an improvement of restorative properties is also seen. This article discusses the evolution of the resin-based composite, the recent advancements and the way forward to achieve better materials.